Diagnostic Accuracy and Visual Search Efficiency: Single 8 MP vs. Dual 5 MP Displays. - Krupinski, Elizabeth (Journal of Digital Imaging, 2017)
This study compared a single 8 MP vs. dual 5 MP displays for diagnostic accuracy, reading time, number of times the readers zoomed/panned images, and visual search. Six radiologists viewed 60 mammographic cases, once on each display. A sub-set of 15 cases was viewed in a secondary study using eye-tracking. For viewing time, there was significant difference ( F = 13.901, p = 0.0002), with 8 MP taking less time (62.04 vs. 68.99 s). There was no significant difference ( F = 0.254, p = 0.6145) in zoom/pan use (1.94 vs. 1.89). Total number of fixations was significantly ( F = 4.073, p = 0.0466) lower with 8 MP (134.47 vs. 154.29). Number of times readers scanned between images was significantly fewer ( F = 10.305, p = 0.0018) with 8 MP (6.83 vs. 8.22). Time to first fixate lesion did not differ ( F = 0.126, p = 0.7240). It did not take any longer to detect the lesion as a function of the display configuration. Total time spent on lesion did not differ ( F = 0.097, p = 0.7567) (8.59 vs. 8.39). Overall, the single 8 MP display yielded the same diagnostic accuracy as the dual 5 MP displays. The lower resolution did not appear to influence the readers' ability to detect and view the lesion details, as the eye-position study showed no differences in time to first fixate or total time on the lesions. Nor did the lower resolution result in significant differences in the amount of zooming and panning that the readers did while viewing the cases.